Indoxyl Sulfate, a Uremic Endotheliotoxin - Guillaume Lano; Stéphane Burtey; Marion Sallée (Toxins, 2020)
Chronic kidney disease (CKD) is associated with a high prevalence of cardiovascular diseases. During CKD, the uremic toxin indoxyl sulfate (IS)—derived from tryptophan metabolism—accumulates. IS is involved in the pathophysiology of cardiovascular complications. IS can be described as an endotheliotoxin: IS induces endothelial dysfunction implicated in cardiovascular morbidity and mortality during CKD. In this review, we describe clinical and experimental evidence for IS endothelial toxicity and focus on the various molecular pathways implicated. In patients with CKD, plasma concentrations of IS correlate with cardiovascular events and mortality, with vascular calcification and atherosclerotic markers. Moreover, IS induces a prothrombotic state and impaired neovascularization. IS reduction by AST-120 reverse these abnormalities. In vitro, IS induces endothelial aryl hydrocarbon receptor (AhR) activation and proinflammatory transcription factors as NF-κB or AP-1. IS has a prooxidant effect with reduction of nitric oxide (NO) bioavailability. Finally, IS alters endothelial cell and endothelial progenitor cell migration, regeneration and control vascular smooth muscle cells proliferation. Reducing IS endothelial toxicity appears to be necessary to improve cardiovascular health in CKD patients.